Stress, Conscious Self-Regulation, and Examination Success in Engineering Students - Varvara I. Morosanova; Irina N. Bondarenko; Igor Yu. Tsyganov (Вестник Московского университета. Серия 14: Психология)
Background. Examination stress is observed in the majority of students, which emphasizes the relevance of searching for psychological resources facilitating successful examination. Objective. The study had its purpose to reveal the stress level of IT students as well as their universal and special regulatory resources for exam success. Study Participants. The study involved 322 second-year students of a Moscow technical university specializing in information security (Mage = 19.22; SD = 4.64; 29% were female students). Methods. The students completed 4 questionnaires on the “Testograph” platform (https://www.testograf.ru) shortly before the exam session: Self-Regulation Profile (SRP-2020), Brief Acute and Chronic Stress (BACS), Perceived Stress Scale (PSS), Subjective and Objective Uncertainty Stress (SOUS) scale. The data processing also included the results of the examination session. Results. The majority of IT students demonstrated an average level of all the studied types of stress when compared to the data from the all-Russian sample. Differences in student performance are mostly related to the level of acute stress experienced during exam preparation period and to the type of academic discipline. Conscious self-regulation makes a significant positive contribution to examination success in the profile disciplines — mathematics and programming: the higher the level of its development is, the higher the examination grades are. Significant predictors of examination success are regulatory competencies of evaluating results and programming educational activities, as well as regulatory properties of reliability and persistence. Conclusions. Conscious self-regulation is a universal regulatory resource for examination success for students in technical specialties. Acute stress experiences can influence exam performance both positively and negatively. The study has identified the regulatory competencies acting as special resources for examination success.